2001
DOI: 10.1101/gr.159901
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Male and Female Germline Transmission of a Human Chromosomal Vector in Mice

Abstract: A small accessory chromosome that was mitotically stable in human fibroblasts was transferred into the hprt − hamster cell line CH and developed as a human chromosomal vector (HCV) by the introduction of a selectable marker and the 3Ј end of an HPRT minigene preceded by a loxP sequence. This HCV is stably maintained in the hamster cell line. It consists mainly of alphoid sequences of human chromosome 20 and a fragment of human chromosome region 1p22, containing the tissue factor gene F3. The vector has an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…14,15,17 The production of mice harboring a human chromosome(s) showing correct tissue-specific human immunoglobulin gene expression provides the first mouse model addressing the capacity of a human marker chromosome to deliver tissue specific transgene expression. The Ishida and Marynen laboratories have now taken this technology one step further by modifying human marker chromosomes using the Cre/loxP system to introduce genes that were stably expressed following transfer of the modified marker chromosome into mice.…”
Section: Engineering Human Marker Chromosomes and Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,17 The production of mice harboring a human chromosome(s) showing correct tissue-specific human immunoglobulin gene expression provides the first mouse model addressing the capacity of a human marker chromosome to deliver tissue specific transgene expression. The Ishida and Marynen laboratories have now taken this technology one step further by modifying human marker chromosomes using the Cre/loxP system to introduce genes that were stably expressed following transfer of the modified marker chromosome into mice.…”
Section: Engineering Human Marker Chromosomes and Mouse Modelsmentioning
confidence: 99%
“…The Ishida and Marynen laboratories have now taken this technology one step further by modifying human marker chromosomes using the Cre/loxP system to introduce genes that were stably expressed following transfer of the modified marker chromosome into mice. 16,17 …”
Section: Engineering Human Marker Chromosomes and Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach towards constructing HACs, called "top-down", involves fragmentation of already existing chromosomes and generation of smaller mini-chromosomes, where only the three functional chromosomal elements remain. Several studies have shown that minichromosomes can host and allow the expression of large therapeutic genes, be transferred between various mouse and human cell lines and be transmitted through the mouse germ line (Kakeda et al, 2005;Shen et al, 2001;Voet et al, 2001). Though mini-chromosomes have useful properties for application in transgenics, their use in gene therapy is restricted to an ex vivo approach only.…”
Section: Human Artificial Chromosomesmentioning
confidence: 99%
“…Ren et al 2006;Kouprina et al 2013;Kouprina et al 2014). Four different strategies have been developed for the construction of artificial chromosomes (Irvine et al 2005): (i) in the synthetic approach the artificial chromosome is assembled from chromosomal components (Basu et al 2005a;Basu et al 2005b; Harrington et al 1997;Henning et al 1999;Ikeno et al 1998;Ikeno et al 2009;Kaname et al 2005;Kouprina et al 2003;Nakashima et al 2005;Suzuki et al 2006), (ii) the 'top down' method applies the in vivo telomere-associated fragmentation of existing chromosomes (Au et al 1999;Auriche et al 2001;Carine et al 1986;Choo et al 2001;Farr et al 1995;Heller et al 1996;Ishida et al 2000;Katoh et al 2004;Mills et al 1999;Shen et al 2000;Voet et al 2001;Wong et al 2002) , (iii) naturally occurring minichromosomes may be engineered to construct an artificial chromosome (Raimondi 2011), and (iv) de novo chromosome generation can be induced via targeted amplification of specific chromosomal segments (Carl 2004;Csonka et al 2000;Holló et al 1996;Keresö et al 1996;Lindenbaum et al 2004;Praznovszky et al 1991;Tubak et al 1991). To date, two technologies, the 'top down' and the induced de novo chromosome generation approaches have advanced to the point suitable for biotechnological applications.…”
mentioning
confidence: 99%